Effect of Peripartum Supplementation of Rumen Protected Choline and Rumen Protected Fat on Energy Status, Insulin, IGF-1 and Postpartum Fertility in Gir Cows - Chavda, Miteshkumar R.; Savsani, Harish H.; Gadariya, Mahesh R.; Vala, Karsan B.; Dhami, Arjan J.; Karangiya, Vijay K. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The experiment was carried out on 24 advanced pregnant Gir cows in their first to third lactation to study the effects of supplementing rumen protected choline (RPC) and rumen protected fat (RPF) alone and in combination on their blood glucose, plasma insulin and IGF-1 profile, and postpartum fertility. The cows were divided equally into four treatment groups (n = 6 each), T1 (control), T2 (RPC), T3 (RPF) and T4 (RPC and RPF) on the basis of parity, body weight and previous lactation yield. In T1 group, cows were fed with basal diet to meet their nutrient requirement as per Indian Council of Agricultural Research (ICAR) (2013) feeding standards. In T2, each cow was supplemented with RPC @ 45 g/day, in T3 with RPF @ 80 g/d and in T4 with RPC @ 45 g/day + RPF @ 80 g/d along with basal diet of T1, starting from 30 days before expected date of calving to 60 days postpartum. Concentrations of blood glucose, plasma insulin and IGF-1 studied at monthly interval revealed drop in values around day 30 and 60 postpartum with significant differences in both the hormones. Supplementation of RPC and RPF alone or in combination had no significant effect on blood glucose and plasma insulin levels, overall or at any period, except on day 60 postpartum where glucose was significantly higher in RPF group. Plasma concentration of IGF-1 was significantly (p <0.001) lower in T3 and T4 and non-significantly in T2 as compared to control overall and at prepartum and on the day of calving. It was also lowest on day 30 postpartum and fluctuated non-significant between -30, 0 and +60 days in all four groups. First heat postpartum appeared significantly earlier in all three supplementation groups as compared to control (46.17 ± 3.89 to 53.60 ± 4.92 vs.81.67 ± 3.87 days), however reduction in service period and number of services per conception was statistically non-significant. Combined supplement of RPC and RPF had no additional advantage in the study. It can be concluded that RPC or RPF alone can be supplemented in the ration of periparturient Gir cows to improve their energy status and postpartum fertility.